DESKRIPSI KESULITAN SISWA KELAS III DALAM MEMECAHKAN MASALAH PADA MATERI OPERASI HITUNG PERKALIAN - Arisandi, Shilfi; Isrokatun, Isrokatun; Irawati, Riana (Jurnal Pena Ilmiah, 2019)
This research aims to determine students conceptual and procedural abilities in solving problems in multiplication operations and to know the factors that cause students to experience solving problems difficulties in multiplication operations in third grade students in  SDN Sukamaju, SDN Panyingkiran I, and SDN Panyingkiran II. This reseacrh uses descriptive methods with the subject of reseacrh is all third students in SDN  Sukamaju, SDN Panyingkiran I, and SDN Panyingkiran II that amount to one hundred people. Data collection techniques and research instruments that used are diagnostic test, interview guidelines, and teacher performance guidelines. The data analysis technique that used is descriptive statistics. The result of the research indicate that students’ conceptual abilities in the multiplication counting operation material are still fairly low. Students make a alot of mistakes when they’re completing test question. The most mistakes that student do in diagnostic test is in the final result and the least error is in the use of mathematical symbols. Students’ procedural abilities in solving problems in multiplication operation is fairly low. If viewed based on the stages of problem solving, the most ability that mastered by students is the ablity of understand the problem and the least ability is the ability of check back the solution and expend the problem. The factors that caused students to experience difficulties in solving problems in multiplication operations, includes by the factors that cause errors in working on diagnostic test question, internal factors and external factors.